Preliminary experience in age dating with dendrochronological techniques in the olive tree (Olea europaea). Comunidad de Campos de Jahuel, commune of Santa María, Valparaiso, Chile - Cuq Pavez, Emilio; lira, Nicolás; Grimberg, Daniela; González, Francisca (BOSQUE, 2025)
Dendrochronology is a recognized discipline for the study of chronologies and the evaluation of long-term environmental changes. In Chile, using dendrochronological techniques, different tree species have been studied with excellent results. However, there are still species for which we do not know their dendrochronological potential, as is the case of Olivo. The interest of the Campos de Jahuel community in knowing the age of their olive trees and the exact time when they were introduced in the valley, opened the door for an exploratory study of this species with the use of dendrochronological techniques. From a sampling of 15 specimens and the macroscopic analysis of the growth rings, ages of at least 200 years of antiquity were given. This experience was not without methodological difficulties considering the growth characteristics of the olive tree.